OPTIMAL TIME OF LAPAROSCOPIC CHOLECYSTECTOMY IN PATIENTS WITH ACUTE CALCULOUS CHOLECYSTITIS - Zhmur, A.A.; Formanchuk, T.V.; Pokidko, M.I.; Honcharenko, О.V.; Hudz, M.A.; Vovchuk, I.M. (World of Medicine and Biology, 2024)
In order to determine the optimal time from the onset of the disease to laparoscopic cholecystectomy in patients with acute calculous cholecystitis, the treatment results of 107 patients were analyzed. All patients were divided into three groups, depending on the time from the onset of the disease to surgery: the first group included 34 (31.8 %) patients operated on up to 24 hours from the onset of the disease; the second – 49 (45.8 %) patients operated from 24 to 72 hours; third – 24 (22.4 %) patients operated on within ˃72 hours. The data obtained indicate that the optimal time for laparoscopic cholecystectomy in patients with acute calculous cholecystitis was up to 24 hours, which allowed to significantly reduce the duration of surgery, intraoperative blood loss, number of conversions, postoperative hospital stay, duration of antibiotic therapy, postoperative biliary complications rate.
Keywords: gallbladder; acute calculous cholecystitis; laparoscopic cholecystectomy; perivesical tissues; postoperative biliary leakage